PERENCANAAN INSTALASI PENGOLAHAN LIMBAH DOMESTIK DI RUMAH SUSUN KARANG ANYAR JAKARTA - Yudo, Satmoko (Jurnal Teknologi Lingkungan, 2008)
Karang Anyar Flat was built about 30 years ago to provide public cheap and proper housings located in the center of the town. But rightnow condition of the flat is not comfortable anymore, especially the problem on domstic waste treatment instalation. It doesn’t running well; it brings bad smell and most of the pipes broke down. It need a plan to repair the domestic waste treatment instalation and improvement in pipes network system.